Supracondylar Humerus Fracture in Children: A Retrospective Study - Zaman, Shorif Uz; Julfikar, AFM; Islam Nissan, Md Nazmul (Medicine Today, 2025)
Introduction: The most typical kind of distal humeral fracture in children is a supracondylar fracture of the humerus. Depending on the neurovascular injury and Gartland classification, the treatment options are either non-operative or surgical. Which Kirschner pin configuration—crossed pinning or lateral pinning—should be used is still up for debate. Objective: The purpose of our research was to compare the therapeutic outcomes of treating children with cross and lateral pinning for supracondylar humeral fractures. Materials and Methods: Retrospective analysis was done on 80 individuals under the age of 18, who underwent surgery between January 2021 and January 2023 for a supracondylar humeral fracture. For comparison, two treatment modalities—crossed pinning and lateral pinning—were examined. Results: In 66 cases (82.5%) crossed pinning was done, and in 14 patients (17.5%) lateral pinning. During the trauma, the average age was 6.83 years (2–14). When comparing the group treated crosswise to the group treated from the side, there was a substantial increase in the incidence (p = 0.03) of current complaints (53% vs. 33% of patients reported problems, respectively). The following parameters were analyzed: the presence of current neurological complications, the degree of satisfaction with the current function of the limb, the Baumann angle of the operated limb, the flexion deficit in the elbow joint of the operated limb, the Flynn criteria, and the Mayo Elbow Score. No significant differences were found between the types of fixation and any of these parameters. Conclusions: There is ongoing debate in the literature regarding the advantages of lateral or crossing pinning for children's supracondylar humeral fractures. Excellent clinical and functional outcomes are produced by both approaches. Medicine Today 2025, Vol.37 (1): 88-92